A compressed graph representation for services composition. (2018) - Li, Jing; Yan, Yuhong; Zhu, Ming
Service-oriented computing enhances business scalability and flexibility. Providers who expect to benefit from it may bring the explosive growth of web services. As a result, the huge storage required in searching a composition solution may be too much to afford. In this paper, we apply a compressed data structure to tackle this challenging issue. We propose a system model to solves web service composition (WSC) problem. In this model, we use a compressed tree to represent the search graph. This work innovatively solve the composition problem with compressed graph representation. The proposed model is verified through theoretical analysis and experimental study. The obtained experimental results show that this system may handle a large number of web services with small space requirement.